The Effect of Brand Internationalization Strategy on Domestic Consumers’ Purchase Intention: Configuration Analysis Based on Brand Authenticity Perspective - Zhang, Shaoqing; Fang, Yue; Zhang, Yuan; Zhang, Sihong (Frontiers in Psychology, 2022)
Brand internationalization is an important strategy for emerging market enterprises to promote their self-owned brand to the international market. It has practical significance for promoting domestic consumers’ trust and acceptance of international self-owned brand. This paper uses the fuzzy-set qualitative comparative analysis (fsQCA) as the method and 218 consumers in China as the survey subjects. The research focuses on exploring the core factors that stimulate domestic consumers’ purchase intention from the perspective of consumers’ perceived authenticity of brand internationalization (PABI) and how these factors cooperate to affect the driving path of domestic consumers’ high purchase intention. The findings show that (1) country of origin image, quality perception, credibility, and self-identity are the four core factors that stimulate domestic consumers’ purchase intention from the perspective of PABI, but each factor cannot be the necessary condition for high domestic consumers’ purchase intention alone. (2) Three types of conditional configurations constitute the driving path of high domestic consumers’ purchase intention: “country of origin image - self-identity,” “self-identity - credibility,” and “country of origin image - quality perception - credibility.” (3) The potential substitution relationship of the four core factors reflects that emerging market enterprises should choose a targeted driving path to implement brand internationalization strategies; this strategy helps enterprises to enhance domestic consumer trust and acceptance. This study broadens the exploration of brand internationalization through new research methods and perspectives and helps emerging market enterprises to design and implement various targeting, positioning, and segmentation strategies to successfully promote brand internationalization under the contest between globalization and anti-globalization.